Analysis of Base Station Replacement Using the Cost-231 Propagation Model and Stanford University Interim (SUI) on the LTE Network in Pauh District, Padang - Afrizal Yuhanef; Zurnawita; Nadia Pratiwi; Herry Setiawan (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The increase in network traffic is caused by an imbalance between the number of users and the provision of network capacity, causing the decrease of network performance. This is often found in densely populated areas with a large number of users so that the use of cellular access services is fairly high. For this reason, it is necessary to optimize the network, one of which is by replacing existing devices (swap). Site 31140_Lubuk Bukit, Pauh District, Padang is one of the base stations that has a performance issue, which has a low throughput value (±5Mbps) and a high traffic value of 83 GB/day with Flexi Multi Radio device type and sectoral antenna. Therefore, the existing equipment is replaced, from the FMR type to the Airscale type which minimizes the use of sectoral equipment and antenna types (3 sectors) to multisectoral (6 sectors). The measurement process is carried out using two methods, namely the COST-231 propagation model for the frequency of 1800 MHz and the Stanford University Interim (SUI) for the frequency of 2100 MHz then the Key Performance Indicator (KPI) parameters with the parameters of accessibility, retainability, integrity, mobility, usage, propagation loss and receive power. The results showed that the optimization carried out by the swap method could improve the site's performance, namely a decrease in traffic reaching 31.42% and an increase in throughput up to 60% and followed by an increase in other parameters that have met the threshold value.